Dietary total sulfur amino acid requirement for optimal growth performance and carcass characteristics in finishing gilts - J A Loughmiller; Michael D Tokach; Evan C Titgemeyer; I H Kim; J R Bergstrom; J W Smith II; Robert D Goodband; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1996)
Finishing gilts (initially 163 lb) were fed .58% total lysine (.50% apparent digestible) and total sulfur amino acid (TSAA) concentrations of .26,.285, .31, .335, and .36% (.225 to .325% apparent digestible). These values represent TSAA: lysine ratios of 45, 50, 55, 60, and 65%. Results suggest a linear decrease in ADG and ADFI along with poorer F/G with increasing TSAA levels. However, gilts fed .285% TSAA (50% of lysine) had the best ADG and F/G. No effect was observed on any carcass criteria. Based on the results of this study, the TSAA requirement is not greater than .285% total (.25% apparent digestible) or approximately 50% of the lysine requirement.; Swine Day, Manhattan, KS, November 21, 1996
Keywords: Swine day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 772; Swine; Finishing pigs; Growth; Total sulfur amino acids